STUDENTS’ PERSPECTIVE ON ETHICS MANAGEMENT OF HIGHER EDUCATION SYSTEM OF ROMANIA - Silvia PUIU (Management & Marketing)
The article presents the critical perspectives of students from higher education system of Romania on the ethics and ethics management of institutions where they study. Their point of view reflects also their experience but also the image of universities in the common perception. The methodology used a questionnaire on a number of 113 students from more than ten cities and more institutions, from private and public system also. This study was conducted in parallel with another research made on managers’ perspective in order to bring equilibrium and a more realistic image of the ethics management in Romania’s universities. Results reflect the lacks in this system and the poor image in education sector and create numerous opportunities for an improvement by implementing the tools of ethics management. There is an important gap between the two perspectives, both subjective of course, but this reality addresses a lot of questions to debate on, for a considerable change in the way managers use ethics management as a powerful tool to increase their competitiveness on education market.